2003
DOI: 10.1038/nature01409
|View full text |Cite
|
Sign up to set email alerts
|

The double helix and immunology

Abstract: genomic insult. This integrated field is now deciphering the complex regulatory pathways transduced by signalling mechanisms that detect DNA damage and/or arrested DNA replication. As these pathways become better understood, parallel technological gains in gene therapy and therapeutic intervention by rational drug design will offer new strategies for blocking the unwanted consequences of DNA damage, especially cancer.We must remember, however, that while evolution could not have transpired without robust cellu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
18
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 22 publications
0
18
0
Order By: Relevance
“…I n jawed vertebrates, the adaptive immune system is characterized by the exponential diversity of its Ag receptors (1)(2)(3)(4)(5). In contrast to the receptors of the innate immune system that bind relatively invariant pathogen-associated epitopes (6), diverse Ag receptor repertoires allow recognition of novel or divergent epitopes on pathogens or toxins.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…I n jawed vertebrates, the adaptive immune system is characterized by the exponential diversity of its Ag receptors (1)(2)(3)(4)(5). In contrast to the receptors of the innate immune system that bind relatively invariant pathogen-associated epitopes (6), diverse Ag receptor repertoires allow recognition of novel or divergent epitopes on pathogens or toxins.…”
mentioning
confidence: 99%
“…The diversity of Ig, the BCR, is primarily the property of the V domains of the H and L chains (1)(2)(3)(4)(5). Diversity is asymmetrically distributed within each V domain (7,8).…”
mentioning
confidence: 99%
“…Genetic studies (6,7) and algorithmic inferences from biological sequence data (8)(9)(10) have revealed that recombination can occur preferentially within coding sequences, at times with a higher frequency than mutation (11,12). When sequences encoding divergent but related proteins recombine, large distances may be traveled in sequence space relative to random mutation (13)(14)(15)(16) without disturbing function and͞or structure. However, a complete understanding of the underlying relative efficiency of mutation and recombination in accessing nearby or distant regions of sequence space cannot be gained from genomic sequences because these become available only after natural selection has acted.…”
mentioning
confidence: 99%
“…A highly diversified Ig repertoire enables the adaptive immune system to recognize a wide array of ancient and novel pathogens and toxins (1)(2)(3)(4)(5). For the H chain, the focus for combinatorial diversification is CDR-3 (CDR-H3), 5 which is created de novo by the rearrangement and juxtaposition of individual variable (V H ), diversity (D H ), and joining (J H ) gene segments.…”
mentioning
confidence: 99%
“…For the H chain, the focus for combinatorial diversification is CDR-3 (CDR-H3), 5 which is created de novo by the rearrangement and juxtaposition of individual variable (V H ), diversity (D H ), and joining (J H ) gene segments. The location of CDR-H3 at the center of the Ag binding site emphasizes its often fundamental role in Ag recognition (6 -8).…”
mentioning
confidence: 99%